Revisiting Previously Investigated Plants: A Molecular Networking-Based Study of Geissospermum laeve - Fox Ramos A.E. (2017)
This work has been developed with the funding from Cienciactiva, an initiative of the National Council for Science, Technology and Technological Innovation (CONCYTEC) contract 239-2015-FONDECYT. In addition, this work was also supported by the French ANR grant ANR-15-CE29-0001. We express our thanks to Dr. J. Bignon (ICSN) for performing the cytotoxic assays. We also thank K. Leblanc (BioCIS) for her assistance in the preparative HPLC purifications. We are grateful to Dr. M. Wang, Prof. P. Dorrestein, and Prof. N. Bandeira (University of California, San Diego) for developing and making public the GNPS platform.